PENDAMPINGAN PENGGUNAAN BAHAN AJAR MATEMATIKA BRAILLE 3D - Rina Agustina; Nurul Farida; Achyani Achyani; Muhfahroyin Muhfahroyin (Ruang Pengabdian : Jurnal Pengabdian Kepada Masyarakat, 2022)
In learning mathematics so far, low-vision students only use ordinary braille books. The use of this braille book cannot help students to know the real shape of the object being studied. One form of updating teaching materials for low-vision students is the use of 3D media contained in teaching materials. The objectives of this service activity are: (1) Provide knowledge about teaching materials needed for low vision students, (2) Provide assistance to teachers at SLB Negeri Metro in using 3D Braille mathematics teaching materials, and (3) Provide knowledge of making 3D media on teaching materials braille math. The form of activity provided in this activity is in the form of assistance in the use of 3D Braille mathematics teaching materials. From this activity, the teacher gains knowledge about: (1) how to prepare teaching materials, (2) preparation of learning tools, (3) the use of mathematics teaching materials, and (4) the use of 3D braille mathematics teaching materials. The understanding obtained by the teacher after participating in this service activity was: (1) 100% for the preparation of teaching materials and the use of 3D Braille mathematics teaching materials, (2) 96% for the preparation of learning tools and the use of mathematics teaching materials. Before the activity was held, the teacher only knew about the usual use of braille teaching materials and had some obstacles in compiling independent teaching materials. After this activity, the teacher became more aware of how to use Braille mathematics teaching materials, which could be accompanied by 3D media to make it easier for low-vision students to understand. In addition, teachers also understand more about how to compile teaching materials and learning tools.Keywords: accompaniment; braille;teaching materialAbstrakDalam pembelajaran matematika selama ini, siswa low vision hanya menggunakan buku braille biasa. Penggunaan buku braille ini tidak dapat membantu siswa untuk mengetahui bentuk nyata dari benda yang dipelajari. Salah satu bentuk pembaruan bahan ajar bagi siswa low vision adalah penggunaan media 3D yang terdapat pada bahan ajar. Tujuan kegiatan pengabdian ini adalah: (1) Memberikan pengetahuan tentang bahan ajar yang dibutuhkan bagi siswa low vision, (2) Memberikan pendampingan guru di SLB Negeri Metro dalam menggunakan bahan ajar matematika braille 3D, (3) Memberikan pengetahuan pembuatan media 3D pada bahan ajar matematika braille. Bentuk kegiatan yang diberikan dalam kegiatan ini berupa pendampingan penggunaan bahan ajar matematika braille 3D. Dari kegiatan ini guru memperoleh pengetahuan tentang : (1) cara penyusunan bahan ajar, (2) penyusunan perangkat pembelajaran, (3) penggunaan bahan ajar matematika, (4) penggunaan bahan ajar matematika braille 3D. Pemahaman yang diperoleh guru setelah mengikuti kegiatan pengabdian ini sebesar : (1) 100 % untuk materi penyusunan bahan ajar dan penggunaan bahan ajar matematika braille 3D, (2) 96% untuk materi penyusunan perangkat pembelajaran dan penggunaan bahan ajar matematika. Sebelum diadakan kegiatan, guru hanya mengetahui penggunaan bahan ajar braille secara biasa dan memiliki beberapa hambatan dalam menyusun bahan ajar mandiri. Setelah adanya kegiatan ini, guru menjadi lebih mengetahui dalam menggunakan bahan ajar matematika braille dapat disertai media 3D agar lebih mudah dipahami oleh siswa low vision. Selain itu, guru juga lebih memahami tentang cara menyusun bahan ajar dan perangkat pembelajaran.DOI: https://doi.org/10.23960/rp/v2i1.hal.87-93